Instructors’ Acceptance of Roblox Studio for Informatics Education: An Extended TAM with Perceived Risk - Ayu Permata Sari; Rizki Hikmawan (Journal of Informatics and Vocational Education, 2026)
The increasing integration of immersive digital platforms in education has created new opportunities for game-based learning; however, tutors’ acceptance of game development platforms remains insufficiently explored in empirical research. This study investigates the factors influencing tutors’ intention to adopt Roblox Studio as a learning platform in informatics education by applying an Extended Technology Acceptance Model (TAM) integrated with perceived risk. Data were collected from 125 informatics tutors in Indonesia using a structured questionnaire and analyzed using Covariance-Based Structural Equation Modeling (CB-SEM) with a Robust Maximum Likelihood estimator. The results indicate that the proposed model explains 84.3% of the variance in behavioral intention to use Roblox Studio. Perceived Ease of Use significantly influences Perceived Usefulness, while Attitude Toward Using emerges as the strongest predictor of tutors’ adoption intention. Interestingly, Perceived Ease of Use and Perceived Usefulness do not significantly affect tutors’ attitudes, suggesting that pedagogical considerations may play a more dominant role than purely technical factors in technology adoption decisions. Furthermore, perceived risk does not significantly reduce adoption intention, indicating that tutors tend to prioritize the pedagogical benefits of immersive platforms over potential technological concerns. This study contributes to the literature by extending the Technology Acceptance Model within the context of game-development platforms and providing empirical insights into tutor perspectives in game-based learning adoption. The findings offer practical implications for educators and institutions seeking to integrate immersive digital platforms into informatics education.